Effect of Rock Mass Properties on Coupled Thermo-Hydro-Mechanical Responses at Near-Field Rock Mass in a Heater Test–A Benchmark Sensitivity Study of the Kamaishi Mine Experiment in Japan - Yoo, Hwajung; Yoon, Jeonghwan; Min, Ki-Bok (Journal of nuclear fuel cycle and waste technology (Online), 2023)
Coupled thermo-hydraulic-mechanical (THM) processes are essential for the long-term performance of deep geological disposal of high-level radioactive waste. In this study, a numerical sensitivity analysis was performed to analyze the effect of rock properties on THM responses after the execution of the heater test at the Kamaishi mine in Japan. The TOUGHFLAC simulator was applied for the numerical simulation assuming a continuum model for coupled THM analysis. The rock properties included in the sensitivity study were the Young’s modulus, permeability, thermal conductivity, and thermal expansion coefficients of crystalline rock, rock salt, and clay. The responses, i.e., temperature, water content, displacement, and stress, were measured at monitoring points in the buffer and near-field rock mass during the simulations. The thermal conductivity had an overarching impact on THM responses. The influence of Young’s modulus was evident in the mechanical behavior, whereas that of permeability was noticed through the change in the temperature and water content. The difference in the THM responses of the three rock type models implies the importance of the appropriate characterization of rock mass properties with regard to the performance assessment of the deep geological disposal of high-level radioactive waste.